1966
DOI: 10.1093/genetics/54.3.911
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Genes Controlling Synthesis of the Galactose Pathway Enzymes in Yeast

Abstract: HE genetic control of synthesis of the galactose pathway enzymes in Saccharomyces cerevisiae conforms in certain respects to the operon model proposed by JACOB and MONOD (1961) for the ,&galactosidase system of E. coli, and shown by BUTTIN (1963a, b) to be valid for the E. coli galactose system as well. Three closely linked structural genes specify the galactose pathway enzymes, galactokinase, galactose-1-phosphate-uridyl transferase (transferase), and uridine diphosphogalactose-4-epimerase (epimerase) (DOUGL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
34
0

Year Published

1967
1967
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(34 citation statements)
references
References 2 publications
(2 reference statements)
0
34
0
Order By: Relevance
“…Sc99 was a gift of ROGERS YOCUM, Sc258R10 was a gift OfJACQUELINE BROMBERG, and Sc272 was a gift of KUNIHIRO MATSUMOTO. Sc99 was isolated as a Gal+ revertant of a p-GAL4 GAL80 gal3 strain (for details, see DOUGLAS and HAWTHORNE 1966). Sc252 was isolated as a Gal+ revertant of a GAL4 GAL80S"" strain (JOHNSTON and HOPPER 1982).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sc99 was a gift of ROGERS YOCUM, Sc258R10 was a gift OfJACQUELINE BROMBERG, and Sc272 was a gift of KUNIHIRO MATSUMOTO. Sc99 was isolated as a Gal+ revertant of a p-GAL4 GAL80 gal3 strain (for details, see DOUGLAS and HAWTHORNE 1966). Sc252 was isolated as a Gal+ revertant of a GAL4 GAL80S"" strain (JOHNSTON and HOPPER 1982).…”
Section: Methodsmentioning
confidence: 99%
“…T HE GAL4 gene of Saccharomyces cerevisiae encodes a protein that activates transcription of galactose and melibiose catabolic enzyme genes (DOUGLAS and HAWTHORNE 1966;JOHNSTON and HOPPER 1982;LAUGHON and GESTELAND 1982;HASHIMOTO et al 1983). Activation is achieved primarily through two functions of the GAL4 protein; an amino-terminal DNA binding function which positions GAL4 upstream of regulated structural genes (GUARENTE, YOCUM and GIFFORD 1982;JOHNSTON and DAVIS 1984;WEST, YOCUM and PTASHNE 1984;BRAM and KORNBERG 1985;GI-NIGER, VARNUM and PTASHNE 1985;BRAM, LUE and KORNBERG 1986;KEEGAN, GILL and PTASHNE 1986), and a carboxy-terminal "activation" function which interacts with cellular transcription factors (BRENT and PTASHNE 1985;JOHNSTON et al 1986; JOHNSTON, SALMERON and DINCHER 1987;MA and PTASHNE 1987a).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…6,[14][15][16] Second, although a ga17-deleted (i.e., GALT-deficient) yeast stops growing upon addition of galactose to the growth medium, a ga17 ga11 double knockout strain deficient in both GALT and GALK enzyme activities is no longer sensitive to galactose and grows well. 17,18 Third, our laboratory recently demonstrated that galactose challenge to isogenic GALTdeficient (but not GALK-deficient) yeast led to overt manifestation of environmental stress response (ESR). 19 All these studies indicate that gal-1-p is the major, if not sole, culprit for the galactose toxicity observed in GALT-deficient cells.…”
Section: Introductionmentioning
confidence: 99%
“…It is historically interesting that PONTECORVO (1950) in his early studies of Aspergillus postulated clusters of functionally related genes, but that no cases of clearly functionally distinct groupings were found (ROPER 1960;PONTECORVO 1952). Although such clusters are now well known in bacteria (DEMEREC 1964), they have been clearly demonstrated in eucaryotic microorganisms only in the above-cited studies of histidine biosynthesis in Neurospora and yeast and in studies of aromatic synthesis in Neurospora (GROSS and FEIN 1960;GILES 1965;GILES, CASE and PARTRIDGE 1965) and the galactose pathway in yeast (DOUGLAS and HAWTHORNE 1966). It is important to determine if this type of organization is widespread and can be observed in other organisms as well.…”
mentioning
confidence: 99%